Рід Paeonia L. (Paeoniaceae) у флорі України - Шиян, Н.М. (Український ботанічний журнал, 2011)
Изучено видовое разнообразие Paeonia (Paeoniaceae) флоры Украины, включая выращиваемые в культуре виды. В природе в Украине произрастают P. daurica Andrews и P. tenuifolia L., культивируются семь видов рода: P. anomala L., P. caucasica (Schipcz.) Schipcz., P. delaveaya Franch., P. hybrida Pall., P. mascula (L.) Miller, P. lactiflora Pall., P. peregrina Miller. В статье дан конспект рода, перечень изученных образцов из гербариев CHER, CWU, DZN, KW, KWHA, LW, LWKS, MSUD (электронное приложение), предложен ключ для определения видов. The species diversity within the genus Paeonia (Paeoniaceae) in the flora of Ukraine was studied inc luding native and cultivated species. There are two species in the native flora (Paeonia daurica Andrews, P. tenuifolia L.) and seven cultivated species (P. anomala L., P. caucasica (Schipcz.) Schipcz., P. delavayi Franch., P. hybrida Pall., P. mascula (L.) Mill., P. lactiflora Pall., P. peregrina Mill.). A synopsis of Paeonia species in the Ukrainian flora is presented, with an electronic list of the examined herbarium specimens from CHER, CWU, DZN, KW, KWHA, LW, LWKS, MSUD. An identification key for Paeonia species is provided.